Effect of aperture ratio on the cyclic shear behavior of aggregate-geogrid interfaces. Issue 3 (1st June 2020) - Wang, J.; Liu, F.Y.; Zheng, Q.T.; Cai, Y.Q.; Gou, C.F.
Abstract : In order to study the effect of aperture ratio (geogrid aperture size (AS)/average particle size (D50 )) on the shear behavior of aggregate–geogrid interfaces, a series of monotonic direct shear (MDS) tests, cyclic direct shear (CDS) tests and post-cyclic monotonic direct shear (PCDS) tests were carried out on two particle-shaped reinforced interfaces at five values of AS/D50 . The cyclic shear behavior of the two interfaces under three displacement amplitudes is discussed, and the interfacial shear characteristics before and after cyclic shear are analyzed. The test results indicate that four possible cyclic shear behaviors can occur for two reinforced interfaces, including shear hardening (H), cyclic cumulative softening (SI), direct softening (SII) and wave softening (SIII). With increasing amplitude, the cyclic shear response of both interfaces changes from shear hardening to shear softening. The vertical displacements of both interfaces indicate an overall shear contraction trend in the CDS tests. The stiffness of two reinforced interfaces was significantly affected by the displacement amplitude and the ratio AS/D50 . Compared with the maximum dilation of two reinforced interfaces in the MDS tests, the corresponding value increased in the PCDS tests; and the increase is more significant at rounded aggregate-geogrid interfaces.